Del arbol a la mesa - Ring, Susan; Ring, Susan (Mankato, Minn. : Yellow Umbrella Books, 2005)
Presenta el proceso de cosechar y hacer la miel de arce.
Presents a children's book that describes how maple trees are tapped for their sap and how that is made into maple syrup.
Includes index.
Translation of: From tree to table.
Text in Spanish.
Keywords: Maple syrup